Phytochemical and biological characterization of Italian "sedano bianco di Sperlonga" Protected Geographical Indication celery ecotype: A multimethodological approach. (30th March 2020) - Ingallina, Cinzia; Capitani, Donatella; Mannina, Luisa; Carradori, Simone; Locatelli, Marcello; Di Sotto, Antonella; Di Giacomo, Silvia; Toniolo, Chiara; Pasqua, Gabriella; Valletta, Alessio; Simonetti, Giovanna; Parroni, Alessia; et al.
Highlights: "sedano bianco di Sperlonga" PGI celery was investigated by a multi-methodological approach. A detailed phytochemical profile of the edible part (petioles and blade leaves) was obtained. Biogenic amine and mycotoxin low contents confirmed celery quality and freshness. Ethanolic extract of blade leaves showed antimutagenic and radical scavenger power. Abstract: Celery is a widely used vegetable known for its peculiar sensorial and nutritional properties. Here, the white celery ( Apium graveolens L.) "sedano bianco di Sperlonga" PGI ecotype was investigated to obtain the metabolic profile of its edible parts (blade leaves and petioles) also related to quality, freshness and biological properties. A multi-methodological approach, including NMR, MS, HPLC-PDA, GC–MS and spectrophotometric analyses, was proposed to analyse celery extracts. Sugars, polyalcohols, amino acids, organic acids, phenols, sterols, fatty acids, phthalides, chlorophylls, tannins and flavonoids were detected in different concentrations in blade leaf and petiole extracts, indicating celery parts as nutraceutical sources. The presence of some phenols in celery extracts was here reported for the first time. Low contents of biogenic amines and mycotoxins confirmed celery quality and freshness. Regarding the biological properties, ethanolic celery extracts inhibited the oxidative-mediated DNA damage induced by tert -butylhydroperoxide and scavenged DPPH and ABTS radicals.